2020
DOI: 10.1051/matecconf/202032402006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the operation of a refrigeration unit using radiative cooling to maintain the storage temperature in the cold room

Abstract: The results of the research, which show the effect of radiative cooling on the temperature of food storage chamber during the cold season in the cities of Almaty and Kostanay (Kazakhstan) were obtained through computer simulation of the operation cycle. In the installation modelled, pumping circulation of a heat carrier cooled at night in radiators is used. The radiators of the installation cover the entire roof of the cold room (12 m2). Computer simulation shows that the required temperature in the cooled cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Based on the data in [19], it is expected that by the end of the night, the temperature in the cold accumulator will be 5 °C higher than the minimum ambient temperature. Thus, in the conditions considered (Fig.…”
Section: Discussion Of the Results Obtained In The Study Of Energy Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the data in [19], it is expected that by the end of the night, the temperature in the cold accumulator will be 5 °C higher than the minimum ambient temperature. Thus, in the conditions considered (Fig.…”
Section: Discussion Of the Results Obtained In The Study Of Energy Ef...mentioning
confidence: 99%
“…In this study, the heat-transfer agent was not cooled in radiators at night since the dependence of the heat-transfer agent temperature on atmospheric air temperature by the end of the night was studied in [19][20][21][22].…”
Section: Measurement Of Operating Parameters Of the Experimental Unitmentioning
confidence: 99%
“…In paper [16], a computer simulation of the RC refrigeration system used to maintain a temperature of 0 • C in fruit storage was carried out. In this system, the heat transfer liquid was cooled in the radiators, which was stored in the cold accumulator.…”
Section: Introductionmentioning
confidence: 99%
“…This work is a continuation of [16] and is necessary for the development of a refrigeration system for fruit storage. A review of the literature [5][6][7][8][9][10][11][12][13][14][15][16] showed that the study of RC heat transfer processes in winter is based on theoretical models, the correctness of which is confirmed only for the warm period of the year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation